THE IMPACT OF THE FAMILY HOPE PROGRAM IN OVERCOMING COMMUNITY ECONOMIC DIFFICULTIES IN KELAPA LIMA SUB-DISTRICT KUPANG CITY - Reisanty Djami; Heni Sauw; Jessica Hermanus (SEAN Institute, 2023)
This study aims to analyze the impacts that occure from the provision of FHP assistance of the community in Kelapa Lima District, Kupang City. As well as knowing what forms of FHP assistance are given to the community and the role of FHP facilitators in providing assistance to beneficiary communities in the Kelapa Lima sub-district are, Kupang City. The research method used is qualitative using a case study approach with the aim of analyzing the impact of FHP assistance in overcoming the economic difficulties of the sub-district community in Kelapa Lima District, Kupang City. The results showed that the impact of FHP assistance on the community to overcome economic difficulties had positive impact, namely reducing the burden on poor community household which can help families of FHP recipient participants to pay for education and health, as well as community welfare to ensure the nutritional intake of the elderly and disabilities. While the negative impact is that there are informants who are still dependent or too hopeful on this assistance so that they are less willing to try to work.